Preliminary Design of Titanium Dioxide Plant from Ilmenite, Capacity of 55,000 Tons/ Year - Cahyani, Imala Septi, Dr. Ir. Ahmad. M. Fuadi, M.T, Ir. Nur Hidayati, M.T., Ph.D (2017)
Titanium dioxide is an inorganic compound with chemical formula TiO2. Titanium dioxide plant is designed with capacity of 55,000 tons per year. The plant is planned to operate for 330 days per year. Titanium dioxide will be built in 2020 on East Belitung, Bangka Belitung. Titanium dioxide is used as a white pigment (in paints, plastics, rubber, and paper), industry of ceramics, fiber, and cosmetics, also used as catalysts and photocatalysts. The product of titanium dioxide is planned to be distributed for domestic needs. Titanium dioxide-making process is done by reacting ilmenite with chlorine gas that produce TiCl4 using coke as reducing agent in a first fluidized bed reactor solid-gas phase. The process takes place at a temperature of 900°C and a pressure of 1 atm. The output of first Reactor is purified and fed to second Fluidized Bed Reactor that continuously operates at a temperature 1000°C and a pressure of 1 atm. The processes are irreversible reaction and exothermic. This plant is classified as high risk plant. The need for raw materials ilmenite is 18,314.8573 kg/h, chlorine is 4,578.7143 kg/h, and coke is 16,255.0694 kg/h. Utilities include water supply process support for 49,795.3701 kg/hour is obtained from river water. Diesel fuel is 2.3222 m3/hour. Compressed air requirement is 122 m3/h. Electricity demand is obtained from the PLN and generator for backup power is 986.4136 kW, fuel is 9.2860 m3/h. Total land area is 19,770 m2. The availability of raw material of ilmenite is obtained from PT. Timah Tbk. and chlorine gas is imported from abroad. The number of employees is 201 people. The titanium dioxide plant needs 588,594,482,703 IDR of fixed capital. Titanium dioxide needs 320,860,312,440 IDR of working capital. Based on the economic analysis, the plant will get 400,433,669,735 IDR of profit before tax. The plant will get 120,130,100,920 IDR of profit after 30% of tax per year. Number of percent Return of Investment (ROI) before tax and after tax is 68% and 47%, respectively. Pay out Time (POT) before tax and after tax is about 1.28 years and 1.74 years, respectively. Break Even Point (BEP) is 46% and shut down point is 35%. Discounted cash flow (DCF) is 56%. Based on the economic feasibility, it can be concluded that the titanium dioxide plant is considered feasible to be built.